On the locking of dislocations by oxygen in silicon - Senkader, S; Jurkschat, K; Gambaro, D; Falster, R; Wilshaw, P (2001)
Locking of dislocations by oxygen atoms in Czochralski silicon has been investigated both experimentally and theoretically. Experiments were performed at annealing temperatures between 700 and 850°C for different annealing times and different oxygen concentrations. These showed five distinct regimes for the unlocking stress as a function of annealing time. First the unlocking stress increases almost linearly with time and then saturates. The saturation stress, the time needed to reach saturation and the duration of saturation depend on the annealing conditions and oxygen content. Following the saturation a rapid increase and a second saturation of the unlocking stress with increasing annealing time were observed. Finally after long anneals the locking effect is much reduced. From the temperature dependence of the first saturation stress the interaction energy between an oxygen atom and a dislocation has been deduced and it is shown that the change in entropy when an oxygen atom is trapped at a dislocation is significant. The transport of oxygen to dislocations has also been investigated by solving the diffusion equation numerically. For these calculations both trapping and emission of oxygen atoms from the dislocation core have been considered.